Retail Salesperson - Waller T; South Africa; Nafte Debbie (South Africa: Awareness Publishing Group (Pty) Ltd, 2010)
An introduction to the job of Retail Salesperson, describing the work of a reatail salespersonal, the skills and personal qualities required, school subjects that are helpful, and the training and opportunities that are available. The book can help learners to decide if this is a suitable career for them.
Junior Non-Fiction-; Juvenile Literature